2010
DOI: 10.1111/j.1468-1293.2010.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density changes in protease inhibitor-sparing vs. nucleoside reverse transcriptase inhibitor-sparing highly active antiretroviral therapy: data from a randomized trial*

Abstract: ObjectiveThe aim of the study was to compare changes in bone mineral density (BMD) over 144 weeks in HIVinfected patients initiating nucleoside reverse transcriptase inhibitor (NRTI)-sparing or protease inhibitor-sparing highly active antiretroviral therapy (HAART). MethodsSixty-three HAART-naïve patients were randomized to zidovudine/lamivudine 1 efavirenz or lopinavir/ritonavir 1 efavirenz. We performed dual energy X-ray absorptiometry (DEXA) at baseline and at weeks 24, 48, 96 and 144 to evaluate lumbar spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…In Simplification with fixed-dose Tenofovir-Emtricitabine or AbacavirLamivudine in adults with suppressed HIV replication, a cART simplification study in patients with undetectable HIV RNA levels, reductions in BMD were observed in patients randomized to tenofovir/emtricitabine, with improvements in the abacavir/lamivudine arm; osteopenia and osteoporosis were encountered at a higher rate in the tenofovir/emtricitabine arm (8.54 vs. 4.37 events per 100 person-years in the abacavir/lamivudine arm) [44]. Rapid reductions of 2-6% in BMD during the first 24-48 weeks, with subsequent stabilization or improvement up to 192 weeks, have been observed in several studies comparing different cART regimens [28,49,[57][58][59][60][61]. Greater reductions in spine and hip BMD at 48 and/or 96 weeks were observed in patients randomized to tenofovir/emtricitabine versus abacavir/lamivudine [49,57], atazanavir/ritonavir versus efavirenz [57], and lopinavir/ritonavir/zidovudine/lamivudine versus lopinavir/ritonavir/nevirapine [28].…”
Section: Vitamin D Deficiency Combination Antiretroviral Therapy Andmentioning
confidence: 89%
“…In Simplification with fixed-dose Tenofovir-Emtricitabine or AbacavirLamivudine in adults with suppressed HIV replication, a cART simplification study in patients with undetectable HIV RNA levels, reductions in BMD were observed in patients randomized to tenofovir/emtricitabine, with improvements in the abacavir/lamivudine arm; osteopenia and osteoporosis were encountered at a higher rate in the tenofovir/emtricitabine arm (8.54 vs. 4.37 events per 100 person-years in the abacavir/lamivudine arm) [44]. Rapid reductions of 2-6% in BMD during the first 24-48 weeks, with subsequent stabilization or improvement up to 192 weeks, have been observed in several studies comparing different cART regimens [28,49,[57][58][59][60][61]. Greater reductions in spine and hip BMD at 48 and/or 96 weeks were observed in patients randomized to tenofovir/emtricitabine versus abacavir/lamivudine [49,57], atazanavir/ritonavir versus efavirenz [57], and lopinavir/ritonavir/zidovudine/lamivudine versus lopinavir/ritonavir/nevirapine [28].…”
Section: Vitamin D Deficiency Combination Antiretroviral Therapy Andmentioning
confidence: 89%
“…Available data suggest that while BMD may initially decline modestly after the start of HAART, there is then a gradual recovery in BMD over time. This may reflect the observation that BMD declines as HIV diseases progress and that this decline may be stopped and probably gradually corrected with successful HAART [21,22]. A recent study shows that patients taking HAART are at increased risk of developing osteopenia and osteporosis [23].…”
Section: Discussionmentioning
confidence: 97%
“…[37,42,43]. Results from several randomized clinical trials among antiretroviral naive patients have shown that initiation of cART is associated with a decrease in bone mineral density (BMD) of 2%-6% at both the hip and the spine, which occurs within the first year of treatment, with stabilization thereafter [40,[43][44][45][46][47][48][49]. Three trials directly compared TDF/FTC with ABC/3TC and found greater decreases in BMD with TDF/FTC-based treatment [40,43,48].…”
Section: Toxicity Issuesmentioning
confidence: 99%